2001
DOI: 10.1007/s002800000256
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and cerebrospinal fluid penetration of phenylacetate and phenylbutyrate in the nonhuman primate

Abstract: These data indicate that PA and PB penetrate well into the CSF after i.v. administration. There may be an advantage to administration of PB over PA, since the administration of PB results in significant exposure to both active compounds. Clinical trials to evaluate the activity of PA and PB in pediatric central nervous system tumors are in progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…However, a similar trend was found also in our recent open pilot study. 10 Regarding our present data, it may be not by chance that the patient (P4) with the highest mean increase in SMN transcript levels showed also the more obvious improvement in muscle strength and the case with the lowest mean increase (P6 who has taken a 33% reduced dosage) had no change in muscle strength. Further data on the effect of PB on muscle strength will be provided by the ongoing placebo-controlled double-blind clinical trial.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, a similar trend was found also in our recent open pilot study. 10 Regarding our present data, it may be not by chance that the patient (P4) with the highest mean increase in SMN transcript levels showed also the more obvious improvement in muscle strength and the case with the lowest mean increase (P6 who has taken a 33% reduced dosage) had no change in muscle strength. Further data on the effect of PB on muscle strength will be provided by the ongoing placebo-controlled double-blind clinical trial.…”
Section: Discussionmentioning
confidence: 65%
“…9 Recently, evidence was given that PB can cross the blood -brain barrier. 10 A drawback to the use of PB is its short-half life (0.8 -1 h). Previous pharmacokinetic studies have shown rapid changes in serum levels of PB in treated subjects with Phenylbutyrate increases SMN expression in vivo C Brahe et al sickle cell disease.…”
Section: Discussionmentioning
confidence: 99%
“…penetrate well into cerebrospinal fluid (Berg et al, 2001); therefore, the findings in this study suggest a great potential role for 4-PBA as a therapeutic agent to restore memory function in AD.…”
Section: Discussionmentioning
confidence: 91%
“…administration in nonhuman primates. 29 These data raise the possibility that PBA could stimulate SMN expression in motor neurons.…”
Section: Discussionmentioning
confidence: 97%